Potencial pedagógico do sensoriamento remoto nas escolas de educação básica da região metropolitana de Feira de Santana - Bahia - Silva, Ana Paula Amorim da (2013)
The introduction of new technologies in education rises as a teaching strategy needed in a progressively technological society that communicates increasingly faster. In this context the use of Remote Sensing becomes more useful in teaching, and the increasing application of Remote Sensing in Geography textbooks can attest this statement. This dissertation aimed to test, develop and implement educational resources to contribute to the school use of Remote Sensing in Elementary Education II (6th to 9 th year) and in the 1st year of High School. Therefore, two articles were prepared: i) Educational Potential of Remote Sensing as a teaching resource in Elementary Education II; ii) The insertion of new technologies in education: the Remote Sensing in the 1st year of High School. The research was conducted by analyzing the use of technologies for Basic Education setting off from theoretical foundations on the teaching of Geography, Cartography and Remote Sensing. As a conclusion of the research it was observed that activities involving teaching resources with Remote Sensing have great interdisciplinary potential, collaborating in teaching and learning, arousing interest and sharpening the students' creativity. Thus, it is expected to expand the look of basic education teachers for the increasing possibility of using Remote Sensing in their classes. That this study is useful not only for the five schools in the Metropolitan Region of Feira de Santana inserted in the search, but that this experience can be widespread and extended to all the regional school system.